Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1073/pnas.1901274116
|View full text |Cite
|
Sign up to set email alerts
|

A nanoelectronics-blood-based diagnostic biomarker for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS)

Abstract: There is not currently a well-established, if any, biological test to diagnose myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). The molecular aberrations observed in numerous studies of ME/CFS blood cells offer the opportunity to develop a diagnostic assay from blood samples. Here we developed a nanoelectronics assay designed as an ultrasensitive assay capable of directly measuring biomolecular interactions in real time, at low cost, and in a multiplex format. To pursue the goal of developing a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 52 publications
2
63
0
1
Order By: Relevance
“…In a recent study by Davis and colleagues, blood cells from ME patients were reported to display a unique impedance pattern in response to hyperosmotic stress suggesting that a nano-electronic impedance sensor could be used in a diagnostic test for ME (38). We find that the GO: Response to osmotic stress was associated with INMEST treatment, and genes involved include the Bcl2 family member BAX, upon treatment ( Fig.…”
Section: Transcriptional Programs Altered In Me Patients Treated By Imentioning
confidence: 58%
See 1 more Smart Citation
“…In a recent study by Davis and colleagues, blood cells from ME patients were reported to display a unique impedance pattern in response to hyperosmotic stress suggesting that a nano-electronic impedance sensor could be used in a diagnostic test for ME (38). We find that the GO: Response to osmotic stress was associated with INMEST treatment, and genes involved include the Bcl2 family member BAX, upon treatment ( Fig.…”
Section: Transcriptional Programs Altered In Me Patients Treated By Imentioning
confidence: 58%
“…It is likely important to improve the diagnostic accuracy of ME and ensure more homogenous group of patients included in order to sharpen our ability to understand the underlying pathology in ME, subdivide patient groups and test treatment strategies in these different subgroups accordingly. The recent advances in diagnostic tests are promising in this regard (38). We hope that this work will inspire others to further investigate the immune/microbe interface and the failure to induce disease tolerance in ME and hopefully this increased attention will lead to some further relief to the millions missing due to this devastating condition.…”
Section: Discussionmentioning
confidence: 86%
“…However, when all three tests were combined using multiple logistic regression, we found very high sensitivity and specificity, with only two from a total of 43 samples (one patient and one control) being misclassified. Except for the recently reported lymphocyte impedance response to salt stress [31], this combination of three tests (lymphocyte death rate, lymphoblast mitochondrial respiratory function and lymphoblast TORC1 activity) thus achieves better accuracy and reliability (sensitivity, specificity and AUC) for discriminating ME/CFS than has been previously reported using other blood-based molecular tests [20][21][22][23].…”
Section: Discussionmentioning
confidence: 74%
“…For patients, physicians and the health care system, this diagnosis-that depends on exclusion of other illnesses-is a long, frustrating and potentially expensive process. Suitable diagnostic biomarkers have not yet been identified, although a recent report of an altered electrical impedance response to salt stress in patient lymphocytes looks highly promising [31]. We reported, in an accompanying paper, that ex vivo lymphocytes from ME/CFS patients exhibit an elevated death rate in culture after recovery from frozen storage and that lymphoblastoid cell lines (lymphoblasts) isolated from them exhibit multiple mitochondrial and cellular stress signalling abnormalities.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation